Impact of the guard grill on the integral and local characteristics of an axial fan - Alič, Gregor (Strojniški vestnik, 2008)
This paper presents the impact of the guard grill (GG) on the integral characteristic (IC) and local aerodynamic properties of the outflow of an axial fan (AF). The study of the GG's impact was conducted using measurements and numeric modelling at the integral and local levels. Measurements of IC were performed according to the ISO 5801 standard and the local velocity field was measured by using a five-hole probe. Numeric simulations of the machine's local characteristics were made in the same working conditions of the fan. The comparison of results was used in the analysis of the GG's impacton the fan's efficiency and in the analysis of the feasibility of the CFD modelling of flow conditions of the GG.
Keywords: ventilatorji; zaščita